Dual human immunodeficiency virus type 1 infection and recombination in a dually exposed transfusion recipient. The Transfusion Safety Study Group. - Diaz, R S (1995)
We studied a case in which a 2-month-old premature infant was concurrently transfused with packed erythrocytes from two different human immunodeficiency virus type 1 (HIV-1)-seropositive donors in late 1984. The two donors also each singly infected a second infant. Inspection of sequences from portions of the HIV-1 genomes in each of the two donors showed a close relationship to the strain in their respective singly exposed recipients. Inspection of sequences from the dually exposed recipient provided evidence of an individual simultaneously infected with two distinct HIV-1 strains, as well as recombination of the two strains in vivo.